Pengaruh Media Audio Visual terhadap Kemampuan Menyimak Cerita Kelas V SD Negeri 68 Kota Bengkulu - Melza Ayuni Sari; Daimun Hambali; Resnani Resnani (Universitas Bengkulu, 2019)
This research aims to determine the effect of the use crossword puzzle media on the ability of vocabulary mastery of second grade students SDN 68 City of Bengkulu. This research is a quantitative research. The research method used is Quasi Experimental Design with The Matching Only Pretest-Posttest Control Group Design. The population in this study is all students of class II SDN in Bengkulu City that accredited A and use curriculum KTS. Sampling technique with Cluster Random Sampling. The sample obtained is SDN 68 Kota Bengkulu with the number of samples consisting of class V A and V B . Data of this research are analyzed by using inferential analysis that is uji t. From the result of the research, the result of t with thitung is 2,43 and t tabel value with significant level 5% equal to 2,04. So with thitung (2,43)> ttabel (2,04). The calculated value obtained is greater than the value of ttabel so that H0 rejected and Ha accepted. The value of thitung obtained is greater than the ttabel value then it can be concluded that there is influence of media use of audio visual to the ability to listen the story on the student of class V in SDN 68 city of Bengkulu.